Analysis of the ability to use partitive articles among the students of French language education program at UNIMED - Mukti, Sharina; Soraya, Tengku Ratna (UNIB Press, 2024)
Ability Analysis, partitive article, student. In writing French language, to make sentences you need articles. The types of articles are definite/indefinite articles and partitive articles, articles are used before nouns and can be counted or cannot be counted. Unimed 3rd-semester students have difficulty using partitive articles. an example is that there are still students who use definition or in-definition articles. Unimed 3rd-semester students have difficulty using partitive articles. an example is that there are still students who use definition or in-definition articles. This research uses a qualitative descriptive approach, according to Mukhtar (2013:10) the data from this research are Unimed third-semester students. The results of this research are that from the tests carried out there were 75% of students e incompetent, 16% were quite competent and 9% were competent.